EFFECT OF COMMUNITY ACTIVITIES IN CONTROL OF VECTORS OF AEDES AEGYPTI MOSQUITO (4M) TOWARDS JENTIC EXISTENCE (CI) IN TLUMPU AND TANJUNGSARI VILLAGE SUKOREJO SUB DISTRICT BLITAR CITY - Ratri, Yulia; Ema Mayasari; Intan Fazrin (Universitas STRADA Indonesia, 2018)
The increase and spread of dengue cases can be caused by changes in population density and mobility, climate change and surrounding environmental conditions. Data from the Ministry of Health shows an increase in dengue fever cases throughout Indonesia. DHF can be controlled by mosquito nest eradication (PSN) activities. The purpose of this study was to determine the effect of community activity in Aedes Aegypti (4M) mosquito vector control on larvae (CI) in Tlumpu Village and Tanjungsari Village, Sukorejo District, Blitar City. Analytical survey research method with cross sectional approach. The study population consisted of all family heads in Tlumpu Village totaling 1,252 families and TanjungsariVillage totaling 2,792 households. The sample in this study amounted to 93 families in the village of Tlumpu and 97 families in the village of Tanjungsari. The sampling technique used is Proportional Random Sampling. The free variable is community activity in controlling the Aedes Aegypti mosquito vector while the bound variable is larvae. Data was collected by questionnaire and tested by the Logistic Regression test. The results showed that the majority of respondents had a level of activity with sufficient categories, namely 59 respondents (60.8%) and most of the respondents in Tanjungsari Village had houses that were not larvae, 58 respondents (59.8%) out of a total of 97 respondents. Tlumpu village shows that the majority of respondents had a level of activity with sufficient categoriesof 57 respondents (61.31%) and according to observations of larva's existence showed that some respondents had houses with non-larva free categories, namely 52 respondents (55.9%) out of a total of 93 respondents . There is an influence of community activity in controlling the Aedes Aegypti mosquito vector against larvae in Tanjungsari Village and Tlumpu Village, Blitar City It is expected tosubmit inputs, criticisms and suggestions regarding various matters related to the activity of the community in controlling mosquito vectors to the existence of larvae so that improvements can be made.